2015
DOI: 10.1128/aac.01208-15
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action of Nitric Oxide-Releasing Chitosan Oligosaccharides against Pseudomonas aeruginosa under Aerobic and Anaerobic Conditions

Abstract: Chitosan oligosaccharides were modified with N-diazeniumdiolates to yield biocompatible nitric oxide (NO) donor scaffolds. The minimum bactericidal concentrations and MICs of the NO donors against Pseudomonas aeruginosa were compared under aerobic and anaerobic conditions. Differential antibacterial activities were primarily the result of NO scavenging by oxygen under aerobic environments and not changes in bacterial physiology. Bacterial killing was also tested against nonmucoid and mucoid biofilms and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 61 publications
1
56
0
1
Order By: Relevance
“…Infections caused by P. aeruginosa also often occur in patients already battling with more severe illness, e.g., extensive trauma, burns, or malignancy [59]. It is very important to examine the antimicrobial effect of NO against this particular strain of bacteria because P. aeruginosa possesses NO reductase enzyme that may enable the bacteria cells to metabolize and deactivate NO, by converting NO to nitrous oxide (N 2 O) and ultimately to nitrogen [6062]. On the other hand, the primary bacterium associated with persistent and complicated catheter-associated urinary tract infections (CAUTIs) is P. mirabilis [3,63,64], which is also known for its ability to elevate urine pH, induce calcium/magnesium phosphate precipitation and produce mature crystalline biofilms [3,63,65].…”
Section: Resultsmentioning
confidence: 99%
“…Infections caused by P. aeruginosa also often occur in patients already battling with more severe illness, e.g., extensive trauma, burns, or malignancy [59]. It is very important to examine the antimicrobial effect of NO against this particular strain of bacteria because P. aeruginosa possesses NO reductase enzyme that may enable the bacteria cells to metabolize and deactivate NO, by converting NO to nitrous oxide (N 2 O) and ultimately to nitrogen [6062]. On the other hand, the primary bacterium associated with persistent and complicated catheter-associated urinary tract infections (CAUTIs) is P. mirabilis [3,63,64], which is also known for its ability to elevate urine pH, induce calcium/magnesium phosphate precipitation and produce mature crystalline biofilms [3,63,65].…”
Section: Resultsmentioning
confidence: 99%
“…66,103 It has been clearly demonstrated that NO releasing/generating polymers can have strong bactericidal effects, 19,146,147,162,201,227,283,284 even for bacteria that are able to metabolize and deactivate NO, such as P. aeruginosa , that possesses NO reductase enzyme that converts NO to nitrous oxide (N 2 O) and ultimately nitrogen (N 2 ). 86,201,219 Of note, NO possesses broad-spectrum antibacterial activity against both gram-positive and gram-negative bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). 219,281 Moreover, the dose of NO required to kill bacteria (e.g., 200 ppm of gaseous NO) 281,282,285 does not show any cytotoxic effects in human dermal fibroblasts when exposed for 48 h. 216,220 In addition to its bactericidal activity at high dosage, low levels of NO (picomolar to nanomolar range in solution phase) 286 also serve as a key mediator that minimize planktonic bacteria adhesion and colonization, as well as disperse mature biofilm and release the bacteria trapped in the EPS film back to their planktonic state.…”
Section: Applications Of No Releasing/generating Polymers For Preparimentioning
confidence: 99%
“…Our lab has previously developed a number of biopolymer scaffolds capable of storing and releasing NO over extended periods to provide targeted therapeutic doses. 8,37,38,47 For example, NO donor-modied b-cyclodextrin exhibited the ability to eradicate bacteria while eliciting minimal cytotoxicity towards mammalian cells, 38 making it an appealing method for therapeutic NO delivery. In this work, the NO-releasing propylamine-modied variant (CD-PA/NO) was selected due to its ability to deliver high NO payloads (0.61 AE 0.05 mmol mg À1 ) with a moderate half-life (1.73 AE 0.24 h).…”
Section: Diffusion From An Extended-release Macromolecular No Donormentioning
confidence: 99%
“…1,3,5 Biolms hinder drug diffusion, alter bacterial metabolism, and increase tolerance towards traditional antibiotics. 1,8,9 As such, severe chronic infections persist in the lungs of CF patients, requiring the constant administration of antibiotics (e.g., colistin and tobramycin) to mitigate infections and prolong the lives of those afflicted with CF. 3,10,11 The continuous administration of antibiotics required to combat these chronic infections has led to the rapid rise of multi-drug resistant (MDR) bacteria in the CF community, necessitating the development of novel therapeutics.…”
mentioning
confidence: 99%